Anne Orthwood's bastard : sex and law in early Virginia - Pagan, John Ruston (Oxford University Press, 2003)
"Anne Orthwood's Bastard" tells the story of a maidservant from Bristol, England who emigrated to Virginia's Eastern Shore in 1662, became pregnant by a caddish nephew of a colonial politician, and died in childbirth, leaving an illegitimate son and a host of knotty legal problems. Through a study of the four cases stemming from this birth and the people involved, Pagan uses the community's response to illuminate the emerging distinctiveness of early American law. He argues that the peculiar structure of Virginia's economy and labour system accounts for many of the differences between colonial and English law, and contends that Virginia leaders skilfully shaped legal doctrines and institutions to serve their own agenda.